60.0k views
3 votes
Answer !!!! Please!!!!!

Answer !!!! Please!!!!!-example-1
User Myluco
by
4.2k points

2 Answers

3 votes

Answer:

C

Explanation:

Given

(3 +
√(2))(3 -
√(2))

Note these are the factors of a difference of squares

a² - b² = (a + b)(a - b)

with a = 3 and b =
√(2), hence

(3 +
√(2))(3 -
√(2))

= 3² - (
√(2)

= 9 - 2

= 7 → C

User Martin Suchan
by
5.0k points
5 votes

Answer:

(3 + √2)(3 - √2) = 7 ⇒ answer (c)

Explanation:

* Lets study the question

- It is a multiplication of two conjugate binomials

- The meaning of conjugate is two binomials have same numbers

with different middle sign ( sum and difference of 2 terms)

- Their product is a difference of two squares

Ex: (a - b) and (a + b)

∵ (a - b)(a + b) = a × a + a × b + (-b) × a + (-b) × b

∴ (a - b)(a + b) = a² + ab - ab - b² ⇒ ab - ab = 0

∴ (a - b)(a + b) = a² - b²

* Lets do that with our question

∵ (3 + √2)(3 - √2) = 3 × 3 + 3 × -√2 + √2 × 3 + √2 × -√2

∵ √2 × -√2 = -2

∴ (3 + √2)(3 - √2) = 9 - 3√2 + 3√2 - 2 ⇒ -3√2 + 3√2 = 0

∴ (3 + √2)(3 - √2) = 9 - 2 = 7

* The answer is (c)

User Alessa
by
4.9k points